Plants used to build and to prepare Guarani houses and templesin Misiones, Argentina - Héctor Keller (Bonplandia, 2008)
A study about the plants used in Guarani communities of Misiones Province, Argentina to buildhouses and temples is presented. Some topics about the abandonment of the traditional normsand materials of construction are discussed